Penerapan Metode Keteladanan Guru dalama Membentuk akhlak Terpuji Peserta Didik di Sekolah Menengah Kejuruan - Sri Hartini Djalasi, Sri Hartini Djalasi; A. Riawarda; Ali Nahruddin Tanal (Indonesian Journal of Islamic Educational Review, 2025)
Research aims to find out how the application of the exemplary method of PAI teachers in forming the commendable morals of students at SMKN 2 Palopo; to find out the commendable morals of students as a result of implementing the exemplary method of PAI teachers at SMKN 2 Palopo; to find out what the obstacles for PAI teachers in applying the exemplary method in forming the commendable morals of students at SMKN 2 Palopo. The research result show that: 1) The application of the PAI teacher's exemplary method in forming students' commendable morals, including: PAI teachers provide examples of arriving on time, teaching polite behavior to anyone, being fair in behavior and actions, teaches an honest attitude in words and actions, directly models an attitude of selfless help, and fosters students' awareness of responsibility. 2) The impact of implementing the exemplary method of PAI teachers on students' morals shows two results, including: a) a questionnaire distributed to 93 students, three categories were obtained, namely 22.11% of students were in the low category, 58.95% of students are in the medium category, and 18.95% of students are in the high category; b) questionnaires distributed to 6 PAI teachers in assessing 48 students, three categories were obtained, namely 8.33% of students were in the low category, 72.92% of students were in the medium category, and 18.75% students are in the high category. 3) The obstacle for PAI teachers in applying exemplary methods in forming students' commendable morals is that internal and external factors influence them.